Ni nanocluster on modified CeO2–ZrO2 nanoporous composite for tri-reforming of methane. Issue 19 (22nd July 2016) - Singha, Rajib Kumar; Das, Subhasis; Pandey, Monica; Kumar, Sachin; Bal, Rajaram; Bordoloi, Ankur
Abstract : Modified Ni-CeO2 –ZrO2 nanoporous catalysts have been synthesized by using a very facile solvothermal approach and urea deposition precipitation method. The catalyst system is highly stable for more than 100 h with almost a constant syngas ratio of 2.1 and >95% methane conversion at 800 °C in the tri-reforming reaction of methane. Abstract : Modified CeO2 –ZrO2 nanoporous composites have been synthesized by using a very facile solvothermal approach and Ni nanoclusters were deposited on this newly developed support by using urea deposition precipitation method. The physico-chemical properties of the prepared catalysts were thoroughly characterized by using X-ray diffraction (XRD), nitrogen physisorption (BET), temperature programmed reduction (TPR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). The prepared materials have been well explored for methane activation with a well-balanced composition of H2 O, CO2 and O2 . The catalysts exhibit promising activity for tri-reforming (H2 O, CO2 and O2 ) of methane with high selectivity towards synthesis gas (a mixture of hydrogen and carbon monoxide). Moreover, reaction parameters also been optimized in detail in terms of temperature, gas hourly space velocity (GHSV) and time on stream (TOS). The study demonstrates that the well synchronised catalyst system is highly stable for more than 100 h with almost a constant syngas ratio of 2.1 and over 95% methane conversion at 800 °C.